2023
DOI: 10.3390/metabo13040542
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Profiles in Older Adults with Frailty: Secondary Analysis from MetaboFrail and BIOSPHERE Studies

Abstract: An altered amino acid metabolism has been described in frail older adults which may contribute to muscle loss and functional decline associated with frailty. In the present investigation, we compared circulating amino acid profiles of older adults with physical frailty and sarcopenia (PF&S, n = 94), frail/pre-frail older adults with type 2 diabetes mellitus (F-T2DM, n = 66), and robust non-diabetic controls (n = 40). Partial least squares discriminant analysis (PLS–DA) models were built to define the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 100 publications
(113 reference statements)
1
0
0
Order By: Relevance
“…Of note, recent studies showed that SR and NMDAR are highly expressed in human pancreatic islet β cells [ 87 ], and systemic D-serine administration modulates insulin secretion in a dose-dependent manner [ 88 , 89 ]. Despite we found similar serum D-serine levels between diabetic and non-diabetic subjects, L-serine and L-glutamate were increased in diabetic compared to non-diabetic group, consistently with previous blood metabolomics evidence [ 16 , 17 ]. In line with other studies [ 90 ], we also observed a positive correlation between serum L-glutamate concentration, BMI and visceral adiposity in both non-frail and frail participants.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, recent studies showed that SR and NMDAR are highly expressed in human pancreatic islet β cells [ 87 ], and systemic D-serine administration modulates insulin secretion in a dose-dependent manner [ 88 , 89 ]. Despite we found similar serum D-serine levels between diabetic and non-diabetic subjects, L-serine and L-glutamate were increased in diabetic compared to non-diabetic group, consistently with previous blood metabolomics evidence [ 16 , 17 ]. In line with other studies [ 90 ], we also observed a positive correlation between serum L-glutamate concentration, BMI and visceral adiposity in both non-frail and frail participants.…”
Section: Discussionsupporting
confidence: 91%